Spatial and temporal variations in Synechococcus microdiversity in the Southern California coastal ecosystem. (23rd November 2020) - Nagarkar, Maitreyi; Wang, Maggie; Valencia, Bellineth; Palenik, Brian
Summary: The Synechococcus cyanobacterial population at the Scripps Institution of Oceanography pier in La Jolla, CA, shows large increases in abundance, typically in the spring and summer followed, by rapid declines within weeks. Here we used amplicon sequencing of the ribosomal RNA internal transcribed spacer region to examine the microdiversity within this cyanobacterial genus during these blooms as well as further offshore in the Southern California coastal ecosystem (CCE). These analyses revealed numerous Synechococcus amplicon sequence variants (ASVs) and that clade and ASV composition can change over the course of blooms. We also found that a large bloom in August 2016 was highly anomalous both in its overall Synechococcus abundance and in terms of the presence of normally oligotrophic Synechococcus clade II. The dominant ASVs at the pier were found further offshore and in the California Current, but we did observe more oligotrophic ASVs and clades along with depth variation in Synechococcus diversity. We also observed that the dominant sequence variant switched during the peak of multiple Synechococcus blooms, with this switch occurring in multiple clades, but we present initial evidence that this apparent ASV switch is a physiological response rather than a change in the dominant population.